Augmenting Feeding Value of Rice Gluten Meal through Dietary Addition of Enzymes in Broilers - Dinani, O P; Tyagi, Pramod Kumar; Mandal, A. B.; Tyagi, Praveen Kumar; Dutta, Narayan (Indian Journal of Animal Nutrition, 2020)
A biological experiment of 42 days duration was undertaken to study the growth performance of broilers. A total of 384, day-old chicks were divided into 12 dietary treatments following 3x4 factorial design having 4 replicates per treatment with 8 birds in each. Twelve experimental diets were prepared by incorporating control, two different levels (15 and 17.5%) of rice gluten meal (RGM), and Â three different types of enzymes namely xylanase (X), protease (P) and multienzymes (M). Data pertaining to the growth performance of birds revealed no significant (P>0.05) difference in RGM levels (15 and 17.5%), but FCR was significantly (P